2006
DOI: 10.1021/jf060950p
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Comparison of the Content of Antioxidant Microconstituents and Several Quality Characteristics in Organic and Conventionally Managed Tomatoes and Bell Peppers

Abstract: Understanding how the environment and production and cultivation practices influence the composition and quality of food crops is fundamental to the production of high-quality nutritious foods. In this 3-year study, total phenolics, percent soluble solids, ascorbic acid, and the flavonoid aglycones quercetin, kaempferol, and luteolin were measured in two varieties of tomato (Lycopersicon esculentum L. cv. Ropreco and Burbank) and two varieties of bell peppers (Capsicum annuum L. cv. California Wonder and Excal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
140
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 50 publications
24
140
3
4
Order By: Relevance
“…A review on variations of antioxidants also in relation to the kind of cultivation [36] does not report any article on the specific issue of polyphenols variation. Total average phenolic content was slightly higher in organic agriculture in a 3-year study (1 and 7% for the two investigated cultivars) [70]. In a 2-year study, on two cultivars, no differences were pointed out [71] and on four cultivars for 3 years no differences were found apart from the behavior of one cultivar along 2 years (one case higher under organic cultivation and in the second higher under conventional cultivation) [72].…”
Section: Effect Of Managementmentioning
confidence: 99%
“…A review on variations of antioxidants also in relation to the kind of cultivation [36] does not report any article on the specific issue of polyphenols variation. Total average phenolic content was slightly higher in organic agriculture in a 3-year study (1 and 7% for the two investigated cultivars) [70]. In a 2-year study, on two cultivars, no differences were pointed out [71] and on four cultivars for 3 years no differences were found apart from the behavior of one cultivar along 2 years (one case higher under organic cultivation and in the second higher under conventional cultivation) [72].…”
Section: Effect Of Managementmentioning
confidence: 99%
“…REMBIAŁKOWSKA (2007) realizando estudo na qualidade de produtos orgânicos verificou que esse tipo de produção induz menores teores de nitrato e resíduos de pesticida e maior teor de vitamina C, aminoácidos essenciais e açúcar total. Outros autores também relataram aumento de vitamina C em espécies hortícolas orgânicas, como em couve chinesa, alface e repolho (ISMAIL & FUN, 2003) e tomates (CHASSY et al, 2006), em comparação as convencionais. Segundo CARVALHO & MULLER (1996), a planta de jambu é rica em elementos nutritivos como ferro, e ainda possui as vitaminas B1, B2, niacina, vitamina C, vitamina A e cálcio.…”
Section: Resultsunclassified
“…Benbrook and Greene (2008) point to the higher levels of good fats and antioxidants in organic food products. Others (Chassy et al, 2006;Asami et al, 2003;Heaton 2001;Weibel et al, 2000) have also found a higher antioxidant content in organic crops. In a long-term study, Mitchel et al (2007) found that health-promoting flavonoids in organic products are twice more than in conventional tomatoes.…”
Section: Organic Agriculture and Food Safetymentioning
confidence: 91%